Establishing a highly competitive university: A strategic management perspective - Abdullah, Haim Hilman; Abubakar, Ahmed (Inderscience Publishers, 2019)
The study examines the effects of organisational strategy, organisational structure, transformational leadership, talent management, and technology integration on university performance and the mediating effect of quality culture. A theoretical framework was developed based on the literature. Data were collected through online survey. 269 questionnaires were sent to vice chancellors/presidents. The study used the proportionate random sampling. The partial least squares method was used to test the hypotheses. The result revealed that organisational strategy, organisational structure, transformational leadership, talent management, technology integration, and quality culture had significant positive effects on university performance. Meanwhile, organisational strategy, talent management and technology integration were significantly and positively related to quality culture, but the organisational structure and transformational leadership did not show any significant link. Similarly, quality culture mediated the relationship between organisational strategy, talent management, technology integration and university performance, but it did not mediate the relationship between organisational structure, transformational leadership and university performance.